2015
DOI: 10.15171/ijhpm.2015.73
|View full text |Cite
|
Sign up to set email alerts
|

Examining the potential role of a supervised injection facility in Saskatoon, Saskatchewan, to avert HIV among people who inject drugs

Abstract: Background: Research predicting the public health and fiscal impact of Supervised Injection Facilities (SIFs), across different cities in Canada, has reported positive results on the reduction of HIV cases among People Who Inject Drugs (PWID). Most of the existing studies have focused on the outcomes of Insite, located in the Vancouver Downtown Eastside (DTES). Previous attention has not been afforded to other affected areas of Canada. The current study seeks to address this deficiency by assessing the cost-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The model above has been adopted previously by six costing studies [4, 28, 30–33]. To operationalize the model, the data shown in Table 1 needs to be imputed in excel programing and combined with the reduction in the rate of needle sharing rates in order to calculate the rate of blood borne infection reductions.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The model above has been adopted previously by six costing studies [4, 28, 30–33]. To operationalize the model, the data shown in Table 1 needs to be imputed in excel programing and combined with the reduction in the rate of needle sharing rates in order to calculate the rate of blood borne infection reductions.…”
Section: Methodsmentioning
confidence: 99%
“…For this research, it was necessary to use a model that reflected the effects of using clean injection equipment and safer injecting behaviours in its calculations. Previous SIF cost studies such as those conducted by Bayoumi and Zaric [5], Pinkerton [60], Pinkerton [61], Andresen and Boyd [3], Andresen and Jozaghi [4], Jozaghi and Jackson [30], Jozaghi et al [31]), Jozaghi et al [32]) and Jozaghi et al [33] have concluded that SIFs are able to prevent the risk of new HIV and HCV cases, since there will be a certain number of known non-shared injections as opposed to shared injections outside of the facility.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations